2019
DOI: 10.5603/ocp.2019.0019
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and difficulties during brain radiotherapy planning with hippocampus sparing

Abstract: Radiotherapy (RT) is frequently used in the treatment of primary and secondary brain tumours, as well as in prophylactic cranial irradiation (PCI). The hippocampus plays a key function in the process of remembering, relaying information from short-term to long-term memory as consolidation, and spatial orientation. Sparing the hippocampus during brain radiotherapy aims to prevent hippocampal-dependent cognitive function deterioration.This procedure requires a good knowledge of the brain's radiological anatomy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Further knowledge on the relationship of static fields/arc fields weighting may allow the application of Hsapf-VMAT to other brain tumors. limitation Manual delineation of the hippocampus poses technical challenges for oncologists, medical physicists, dosimetrists and radiation therapists with high inter-observer variability [22,23]. In our oncology centre, to minimize hippocampus contouring uncertainty during treatment planning, hippocampal volume must be delineated by oncologists with at least 5 years of post-specialization experience.…”
Section: Discussionmentioning
confidence: 99%
“…Further knowledge on the relationship of static fields/arc fields weighting may allow the application of Hsapf-VMAT to other brain tumors. limitation Manual delineation of the hippocampus poses technical challenges for oncologists, medical physicists, dosimetrists and radiation therapists with high inter-observer variability [22,23]. In our oncology centre, to minimize hippocampus contouring uncertainty during treatment planning, hippocampal volume must be delineated by oncologists with at least 5 years of post-specialization experience.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly as cancer therapies have improved survival rates, preservation of neurocognitive function and quality of life is increasingly important. However, manual hippocampal contouring can be challenging with high interobserver variability [ 16 , 17 ], and inverse plan optimization can require multiple iterations to fulfill constraints with generation of helping structures. We have shown that automated tools could be integrated into this complex process to improve both efficiency and plan quality.…”
Section: Discussionmentioning
confidence: 99%
“…Automated hippocampal volumes were accurate without any manual intervention in 99% of cases. Knowledge-based planning typically required approximately 10 minutes and yielded HA-WBRT plans that were more frequently adherent to the NRG CC001 protocol than the manually generated plans actually used in that hippocampal contouring can be challenging with high interobserver variability 13,14 , and inverse plan optimization can require multiple iterations to fulfill constraints with generation of helping structures. We have shown that automated tools could be integrated into this complex process to improve both efficiency and plan quality.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly as cancer therapies have improved survival rates, preservation of neurocognitive function and quality of life is increasingly important. However, manual hippocampal contouring can be challenging with high interobserver variability 13,14 , and inverse plan optimization can require multiple iterations to fulfill constraints with generation of helping structures. We have shown that automated tools could be integrated into this complex process to improve both efficiency and plan quality.…”
Section: Discussionmentioning
confidence: 99%